Determinan Keputusan Menjadi Nasabah Jual Beli Valas (Al-Sharf) di Bank Syariah - Musa Musa (Al-Tijary, 2020)
Forex trading is a part of the economic system that has an impact on satisfying the main needs in the life of global and modern society today. Currently, it is not only the foreign exchange market that conducts foreign exchange trading, but Bank Indonesia also holds a foreign exchange market, where foreign exchange banks can carry out foreign exchange transactions with BI. The satisfaction of community needs in this regard is related to product innovation, location, and promotion strategies in forex trading. The purpose is to analyze the effect of product innovation, location, and promotion strategies on the decision to become a foreign exchange customer (sharf) at Bank Syariah Mandiri Pangkalpinang Branch. This research is a quantitative descriptive. The sample is 66 customers. While the analysis technique used is the multiple linear regression test. The results are: (1) There is a significant influence of the product innovation variable on the decision to become a foreign exchange customer; (2) There is no significant effect of location variables on the decision to become a foreign exchange customer; (3) There is a significant influence of promotion variables on the customer's decision to buy and sell foreign currencies.